1983
DOI: 10.1016/s0072-968x(83)80008-4
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren's Contracture—The Role of Fasciotomy

Abstract: This paper summarises the results obtained in 95 patients treated by fasciotomy, defines the indications for this procedure and describes the operative technique. During a period of seven years a total of 95 patients with 137 fingers affected by Dupuytren's Contracture have been treated by fasciotomy. The minimum follow-up is two years. The oldest patient was 79 years and no patient younger that 50 years was accepted for this form of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Recently, enzymatic fasciotomy with collagenase and percutaneous aponeurotomy have shown promising results. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] …”
mentioning
confidence: 99%
“…Recently, enzymatic fasciotomy with collagenase and percutaneous aponeurotomy have shown promising results. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] …”
mentioning
confidence: 99%
“…Complications were limited to tingling in the fingers, resolving after a number of weeks. It was concluded that PCF allows recovery of useful extension, and that even if the results are not permanent, the patients can be treated with the same technique years later [4].…”
Section: Resultsmentioning
confidence: 99%
“…A bending contracture of MCP joint, produced because the aponeurosis' longitudinal cord resembles a string, can be easily compensated for with a transcutaneous incision that leaves only a small (3-5 mm) wound. Independent of the operational technique, a contracture in the PIP joint is always a more serious problem since there are more structures (the central, spiral, Natatory, and Greyson cord) involved in its formation (4,7). Furthermore, the PIP joint, in contrast to MCP, has poor toleration of longlasting contracture.…”
Section: Discussionmentioning
confidence: 99%